Exploring connections between pollinators and human health - Garibaldi, Lucas Alejandro (2022)
1. Pollinator-dependent plants: bees pollinate plants and allow their reproduction. We use the seeds and the fruits they produce. The healthier the pollinators, especially bees, the better the quality of the food. The crops that are more bee-dependent are usually among the richest in terms of nutrients. The diversity of bee species also plays a crucial role in improving pollination and nutrition. 2. Pollinator-derived products: bees provide humans with propolis and honey, but even more important-ly, they are key to the pollination and reproduction of approximately 28,000 medicinal plants. 3. Green spaces and biocultural landscapes: in general, the connection with bees and other pollinators affects people’s happiness. For example, bees maintain plants that are the essence of nature; thanks to them, we can have a walk in nature, observe, and feel good and happy. 4. Clean water, air, and food: bees are good indicators of the quality of our environment. Places with healthy pollinators and bee communities are not likely to be contaminated with chemicals that also harm humans. Hence, a pollinator and bee-friendly environment is also a human-friendly environment.